2020
DOI: 10.7717/peerj.8375
|View full text |Cite
|
Sign up to set email alerts
|

Appetite regulating genes may contribute to herbivory versus carnivory trophic divergence in haplochromine cichlids

Abstract: Feeding is a complex behaviour comprised of satiety control, foraging, ingestion and subsequent digestion. Cichlids from the East African Great Lakes are renowned for their diverse trophic specializations, largely predicated on highly variable jaw morphologies. Thus, most research has focused on dissecting the genetic, morphological and regulatory basis of jaw and teeth development in these species. Here for the first time we explore another aspect of feeding, the regulation of appetite related genes that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Validation of DE genes from RNA-seq was accomplished via real-time quantitative polymerase chain reaction (qPCR), normalized to stably expressed reference genes ( Kubista et al 2006 ). In our previous studies of East African cichlids, we found that validation of reference gene(s) is an essential step as genes only selected from literature are not necessarily the best choice and can vary a lot between different species and tissue types ( Ahi, Singh, et al 2019 ; Ahi, Richter, et al 2019 ; Pashay Ahi and Sefc 2018 ; Ahi et al 2020a , 2020b ). We chose six candidate reference genes with a small log 2 fold change and the lowest coefficient of variation (CV) throughout all the samples ( supplementary table S4, Supplementary Material online).…”
Section: Resultsmentioning
confidence: 99%
“…Validation of DE genes from RNA-seq was accomplished via real-time quantitative polymerase chain reaction (qPCR), normalized to stably expressed reference genes ( Kubista et al 2006 ). In our previous studies of East African cichlids, we found that validation of reference gene(s) is an essential step as genes only selected from literature are not necessarily the best choice and can vary a lot between different species and tissue types ( Ahi, Singh, et al 2019 ; Ahi, Richter, et al 2019 ; Pashay Ahi and Sefc 2018 ; Ahi et al 2020a , 2020b ). We chose six candidate reference genes with a small log 2 fold change and the lowest coefficient of variation (CV) throughout all the samples ( supplementary table S4, Supplementary Material online).…”
Section: Resultsmentioning
confidence: 99%
“…We selected eight candidate reference genes which have been frequently used in different studies of Haplochromine cichlids and have shown high expression levels in various connective tissues including skeletal tissues [10,[30][31][32][33][34][35]. Furthermore, we chose 16 target candidate genes, which are implicated in scale development and morphogenesis (Table 1).…”
Section: Gene Selection Designing Primers and Binding Site Predictionsmentioning
confidence: 99%
“…To quantify the expression levels of the selected target genes, the validation of stable reference gene(s) with least variation in expression across the anterior and posterior scales of different species is a necessary step [51]. The eight candidates were selected from frequently used reference genes in studies of different tissues in East African cichlids [10,[30][31][32][33][34][35]. The candidate reference genes showed variable expression levels in the scales, and from highest to lowest expressed were respectively; actb1, hsp90a, rps11, rps18, hprt1,gapdh, elf1a and tbp.…”
Section: Validation Of Stable Reference Genesmentioning
confidence: 99%
“…Validation of stably expressed gene(s) in every specific experimental conditions (so-called reference genes) is an essential step, in order to calculate the relative gene expression levels of target genes [97][98][99]. In this study, we assessed the expression levels of 8 candidate reference genes in the gut of lepr mutant and wild-type zebrafish, under different feeding conditions.…”
Section: Reference Gene Validationmentioning
confidence: 99%